Cournot duopoly with cost asymmetry and balanced budget specific taxes and subsidies - Olivia Kay (Games, 2024)
This paper extends the Cournot duopoly model by allowing the government to impose firm-dependent specific taxes or subsidies while keeping the budget balanced. It considers two possible government goals: maximizing the social surplus and maximizing the consumer surplus. It shows that, with identical firms, the best government policy is not to intervene. In the case of cost asymmetry, social surplus and consumer surplus maximization goals require opposite strategies: to maximize the social surplus, the government should tax the high-cost firm driving the economy toward monopoly and increasing productive efficiency at the expense of lower production. In the case of consumer surplus maximization, the tax should be imposed on the low-cost firm reducing the gap between the firms' outputs. Such a strategy, however, increases productive inefficiency and reduces the social surplus.
Keywords: 330; Cournot; oligopoly; specific tax